Studi Komparatif Desain Pixiu Tradisional dan Mainan Shenxing Pixiu: Analisis Simbolis, Estetika, dan Fungsi dalam Budaya Kontemporer - Satria Indra Praja Persada; I Made Gede Arimbawa; Irma Rochmawati (Fakultas Desain Universitas Komputer Indonesia, 2025)
Pixiu (貔貅) is one of the mythological creatures originating from Chinese culture, where this creature is believed to bring good luck, wealth and protection, in its development, there has been a change in form from a traditional sacred representation into a modern form such as Shenxing Pixiu (神行貔貅). Shenxing Pixiu itself is a Pixiu toy made by Shenxing Toys where this toy adapts the aesthetics of kawaii (cute). With the differences in this, it encourages a phenomenon, where the existence of this phenomenon encourages this research to be made, this research itself was made with the aim of analyzing the comparison of designs between traditional Pixiu and Shenxing Pixiu toys from the visual aspect, symbolic meaning and shifting functions in the context of popular culture. The research methods used include descriptive-qualitative analysis of design elements and literature studies. The results of this study indicate that Shenxing Pixiu can maintain the core values of traditional Pixiu but with a more commercial and entertaining approach, so that it is more easily accepted by the younger generation. These changes reflect the adaptation of traditional culture to the modern market without losing its original identity.